Low radiotherapy dose is suitable for brain metastases in SCLC compared with high dose - Xu, Liming; Zhang, Kunning; Han, Haonan; Sun, Han; Yuan, Yajing; Wang, Jun; Zhao, Lujun; Wang, Ping (Frontiers in Oncology, 2023)
Objective This study was designed to evaluate the suitable radiotherapy dose in SCLC patients with BM. Methods A retrospective analysis was performed among 121 patients on the prognosis of BM of SCLC who were admitted to our hospital from 2013 to 2023. They all received first line chemotherapy. 80 patients of them received TRT after chemotherapy. The Chi square method was used to compare the categorical data. Univariate survival analysis was estimated by Kaplan Meier method and the logrank was used to compare survival curves between groups. A multivariate prognostic analysis was made by the Cox proportional hazard model. The iOS and iLC of two groups of low dose and high dose were analyzed after propensity score matching (PSM). Results In all the patients, the median follow-up time was 18.6 months (range 6.30 85.7), the 2-year iOS and iLC rates were 15.4% and 70.3%, respectively, and cerebral necrosis occurred in 2 patients. In univariate analysis related to iOS, extracranial disease control (p=0.023), higher DS-GPA (≥2) (p=0.016), immunotherapy (p=0.049), low-dose(p=0.030), and WBRT+SIB (p=0.009) were significantly associated with an increase in survival rate. After PSM, the 2-year iOS of low dose (n=49) was significantly higher than that of high dose (n=49) (P=0.025), while the 2-year iLC was not significantly improved (P=0.267). In DS-GPA < 2 subgroup, the iOS of low dose group was significantly higher than that of high dose group (p=0.019). In the DS-GPA ≥ 2 subgroup, the 2-year iLC of the low dose group was significantly inferior than that of the high dose group (p=0.044). Conclusions The iLC was improved along with increasing radiotherapy dose, but high dose had inferior iOS compared to low dose, while there were not significantly improving iLC when radiotherapy BED >56Gy. But in patients with DS-GPA≥2 subgroup, high dose brought better iLC benefits.